BCL2-modifying factor promotes germ cell loss during murine oogenesis. Issue 5 (May 2016) - Vaithiyanathan, Kavitha; Liew, Seng H; Zerafa, Nadeen; Gamage, Thilini; Cook, Michele; O'Reilly, Lorraine A; Bouillet, Philippe; Scott, Clare L; Strasser, Andreas; Findlay, Jock K; Hutt, Karla J
Abstract: Apoptosis plays a prominent role during ovarian development by eliminating large numbers of germ cells from the female germ line. However, the precise mechanisms and regulatory proteins involved in germ cell death are yet to be determined. In this study, we characterised the role of the pro-apoptotic BH3-only protein, BCL2-modifying factor (BMF), in germ cell apoptosis in embryonic and neonatal mouse ovaries. BMF protein was immunohistochemically localised to germ cells at embryonic days 15.5 (E15.5) and E17.5 and postnatal day 1 (PN1), coincident with entry into the meiotic prophase, but was undetectable at E13.5, and only present at low levels at PN3 and PN5. Consistent with this expression pattern, loss of BMF in female mice was associated with a decrease in apoptosis at E15.5 and E17.5. Furthermore, increased numbers of germ cells were found in ovaries from Bmf −/− mice compared with WT animals at E15.5 and PN1. However, germ cell numbers were comparable between Bmf −/− and WT ovaries at PN3, PN5 and PN10. Collectively, these data indicate that BMF mediates foetal oocyte loss and its action limits the maximal number of germ cells attained in the developing ovary, but does not influence the number of primordial follicles initially established in ovarian reserve.